IMPLEMENTASI SISTEM PENDIDIKAN ISLAM PADA MASA DAULAH ABBASIYAH DAN PADA MASA SEKARANG - Sri Wahyuningsih (Institut Agama Islam Negeri Purwokerto, 2014)
Savvy generation having good morality can evaluate or criticize themselves and their surroundings hence ideas and discoveries for the advancement of Islam in the future will arise. To realize such a condition, it is necessary to improve the curriculum and Islamic education system. It was a fact that the birth of Islam was followed by the birth of Islamic education and teaching.Education and teaching of Islam continued to grow and develop starting from the time of first four-Caliphs to reach its peak at the period of Daulah Abbasiyah. This glory could be reached because Islamic system of education during the Daulah Abbasiyah in Baghdad could bear the heyday of Islam with developments in all fields, especially in the fields of science. Many great and famous scientists of various disciplines aligned with scientists from western countries were born in the era.Â Generasi yang cerdas berakhlakul karimah dapat mengevaluasi atau mengkritik diri dan lingkungannya sehingga melahirkan ide dan penemuanpenemuan untuk kemajuan Islam pada masa yang akan datang, maka perlu penyempurnaan dalam kurikulum dan sistem pendidikan Islam. Sejak lahirnyah agama Islam, lahir pula pendidikan dan pengajaran Islam. Pendidikan dan pengajaran Islam itu terus tumbuh dan berkembang dimulai dari masa khulafaur-rasyidin sampai pada puncaknya yaitu masa Daulah Abbasiyah. Ssistem pendidikan Islam pada masa Daulah Abbasiyah di Baghdad, karena seperti yang kita ketahui bahwa puncak kejayaan Islam dengan perkembangan di segala bidang khususnya dalam bidang ilmu pengetahuan yang sangat pesat sampai melahirkan ilmuwan-ilmuwan besar dan terkenal dalam berbagai disiplin ilmu sejajar dengan ilmuwan dari negarabarat.